Preferensi Konsumen terhadap Produk Ikan Kaleng (Canned Fish) di Pasar Swalayan Hero Bogor - Lusi Fausia; Iis Diatin; Hahang Mugi Raharjo (Buletin Ekonomi Perikanan, 1996)
The objective of this study are (1) to identify the consumers preference to the atributtes of canned-fish products, and (2) to identify the consumers preference to the type of canned-fish products which ideal.The methodology used in the study is case study, and the purposive sampling technique for sampling method as well. Some statistical models that used in this research are Concordance/Kendall Cooeficient Technique, and Multi atributtes models.This study results that consumers preference to the atributte of canned-fish products is ordered by the following considerations: (1) Brand, (2) Taste, (3) Weight, (4) Price, and (5) The type of can. The statistical result indicate that the correlation between Sardines, Mackerels, Tunas, Salmons, and Crabs are significant at 99,5% level of significance, 97,5% for Skipper and 99% for tiram.